Beatrix Potter, Scientist - Metcalf, Lindsay H.; Wu, Junyi, (Graphic designer) (Chicago, Illinois : Albert Whitman & Company, 2020)
"Everyone knows Beatrix Potter as the creator of the Peter Rabbit stories. But before that, she was a girl of science. As a child, Beatrix collected nature specimens; as a young adult, she was an amateur mycologist presenting her research on mushrooms and other fungi to England's foremost experts. Like many women of her time, she remained unacknowledged by the scientific community, but her keen eye for observation led her to an acclaimed career as an artist and storyteller. A beloved author is cast in a new light in this inspiring picture book story"--.
new kids book 2022 summer.
Includes bibliographical references.
Ages 4-8
Keywords: Potter, Beatrix, -- 1866-1943 -- Childhood and youth -- Juvenile literature; Potter, Beatrix, -- 1866-1943 -- Knowledge -- Science -- Juvenile literature; Authors, English -- 20th century -- Biography -- Juvenile literature; Artists -- Great Britain -- Biography -- Juvenile literature